ความรุนแรงของการติดสารเมทแอมเฟตามีนซ้ำของผู้ป่วยใน ณ สถาบันธัญญารักษ์ ที่เคยได้รับการบำบัดการติดสารเสพติด - วรัญญา จิตรผ่อง (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Data from 250 individuals hospitalized for methamphetamine (MA) use treatment at Thanyarak Institute for drug abuse was collected by using 4 sets of questionnaires including 1) General background questionnaire 2) Severity of dependence scale (SDS) Thai version 3) Mini international neuropsychiatric interview - lifetime (M.I.N.I - lifetime) Thai version. Demographic, diagnosis, MA dependence treatment, and family and social variables were assessed for association with severity of MA relapse by using chi-squares statistics and Fisher’s exact test and logistic regression, backward likelihood ratio. Of 250 individuals, 153 (61.2%) were severely dependent on MA at relapse by SDS criteria. The factors associated severe MA relapse by initial analysis are marital status, religion, manic episode, antisocial personality disorder, having psychological problems before hospitalization, persons that one spent most of the time with, family problems, relationship with father, alcohol dependence, marijuana dependence and other substance dependence. However, MA users being forced legally for current rehabilitation had less severity of current MA dependence than those with voluntary admission. Individuals with severe MA dependence relapse were more likely to use hospitalization as method to successfully quit MA before current relapse. Being widow/divorced/separated, never married, receiving current MA treatment voluntarily, having other substance dependence are associated with severe MA relapse when analyzed by using backward logistic regression analysis.